Political responsiveness and centralized religious leaders: lessons from the Catholic Church - Ziegler, Jeffrey (Politics and religion, 2024)
Are centralized leaders of religious organizations responsive to their followers' political preferences over time even when formal accountability mechanisms, such as elections, are weak or absent? I argue that such leaders have incentives to be responsive because they rely on dedicated members for legitimacy and support. I test this theory by examining the Catholic Church and its centralized leader, the Pope. First, I analyze over 10,000 papal statements to confirm that the papacy is responsive to Catholics' overall political concerns. Second, I conduct survey experiments in Brazil and Mexico to investigate how Catholics react to responsiveness. Catholics increase their organizational trust and participation when they receive papal messages that reflect their concerns, conditional on their existing commitment to the Church and their agreement with the Church on political issues. The evidence suggests that in centralized religious organizations, the leader reaffirms members' political interests because followers support religious organizations that are politically responsive.